School food environments associated with adiposity in Canadian children - Fitzpatrick, C; Datta, G D; Henderson, M; Gray-Donald, K; Kestens, Y; Barnett, T A (International Journal of Obesity, 2017)
Background/Objectives: Targeting obesogenic features of children’s environment that are amenable to change represents a promising strategy for health promotion. The school food environment, defined as the services and policies regarding nutrition and the availability of food in the school and surrounding neighborhood, is particularly important given that students travel through the school neighborhood almost daily and that they consume a substantial proportion of their calories at school. Subjects/Methods: As part of the Quebec Adipose and Lifestyle Investigation in Youth (QUALITY) cohort study, we assessed features of school indoor dietary environment and the surrounding school neighborhoods, when children were aged 8–10 years (2005–2008). School principals reported on food practices and policies within the schools. The density of convenience stores and fast-food outlets surrounding the school was computed using a Geographical Information System. Indicators of school neighborhood deprivation were derived from census data. Adiposity outcomes were measured in a clinical setting 2 years later, when participants were aged 10–12 years (2008–2011). We conducted cluster analyses to identify school food environment types. Associations between school types and adiposity were estimated in linear regression models. Results: Cluster analysis identified three school types with distinct food environments. Schools were characterized as: overall healthful (45%); a healthful food environment in the surrounding neighborhood, but an unhealthful indoor food environment (22%); or overall unhealthful (33%). Less healthful schools were located in more deprived neighborhoods and were associated with greater child adiposity. Conclusions: Despite regulatory efforts to improve school food environments, there is substantial inequity in dietary environments across schools. Ensuring healthful indoor and outdoor food environments across schools should be included in comprehensive efforts to reduce obesity-related health disparities.